Anisotropic thermal conductivity of AlGaN/GaN superlattices. (26th November 2020) - Filatova-Zalewska, A; Litwicki, Z; Moszak, K; Olszewski, W; Opołczyńska, K; Pucicki, D; Serafińczuk, J; Hommel, D; Jeżowski, A
Abstract: High thermal conductivity is an important parameter for nitride-based power electronic and deep-UV light emitters. Especially in the latter case short period superlattices and multicomponent alloys are used and the knowledge of the thermal properties of the binary compounds is sufficient. In-plane and cross-plane thermal conductivity of AlGaN/GaN superlattices were measured by differential two-wire 3 ω method in the temperature range from 147 to 325 K. Samples were grown by metalorganic vapor phase epitaxy; the structure quality and accuracy of superlattice structures preparation were verified by means of HRXRD and transmission electron microscopy. It was observed, that value of thermal conductivities decrease with decreasing period thickness, while temperature dependencies differ from each other—in-plane thermal conductivity decreases, and cross-plane—increases with increasing temperature. Callaway method was used for thermal conductivity calculation; dependence of boundary scattering rate on the phonon wavelength was taken into account. Minimum thermal conductivity was added to calculated values to include the influence of high frequency acoustic phonons and optical phonons on the heat transport. Calculations are in good agreement with experimental results.